The Effect of Corporate Governance on the Financial Performance of Beverage Companies in Uganda - Ajak Mabor Khalil (Uganda Christian University, 2024)
The study was conducted in Coca cola bottling company and focused on corporate governance and financial performance of commercial banks in Uganda: A case of Stanbic bank Uganda limited. Research objectives were to; establish the relationship between audit committees and financial performance, establish the relationship between accountability and financial performance and finally, find out the influence of separation of ownership on financial performance of Stanbic bank (Uganda) Limited. A cross sectional survey research design was employed and both quantitative and qualitative approaches were used. Data was collected using questionnaires, interviews and observation, and analyzed using Pearson correlation coefficient and regressions. The study findings revealed that: auditing and financial performance are significantly related; there is a significant relationship between accountability and financial performance of Stanbic bank and; separation of ownership moderately influences financial performance of Stanbic bank Uganda limited. It was recommended that; i) Audit committees should be strengthened and members should devote more time and commitment to perform their oversight function and appointment to the committee should be based on technical competency of the members ii) Regulators and board should ensure enhanced accountability that is, transparency and disclosure for effective market discipline in accordance with professional best practices iii) Shareholders interference with the work of directors should be minimized as much as possible. The study makes an original contribution by suggesting that there is a positive relationship between corporate governance and financial performance of a firm. These insights in explaining the relationships are useful for academic understanding and business and public policy formulations.